Examining the factors influencing medical tourists to seek medical treatment in Klang Valley and Malacca - Wong, Dai Di; Isa, Siti Suriawati; Bidin, Sheena; Kassim, Roslan (Academia Industry Networks, 2022)
This paper aims to examine the factors influencing medical tourists to seek medical treatment in Klang Valley and Malacca. This study employs the theory of Planned Behaviour and the medical tourism dimension (tourism destination, medical tourism cost, and facility and services) to answer the research objectives. Data was collected from 400 medical tourists from private medical tourism hospitals in Klang Valley and Malacca. The data were analysed using SPSS. The findings suggest that only four variables (i.e., subjective norms, perceived behavioural control, medical tourism costs, and quality of facilities and service) influence medical tourists’ seeking medical treatment. This study has theoretical and practical contributions to academics, medical tourism practitioners and industry.